Some Examples of Repetitive, Nonrectifiable Delone Sets - Cortez-Munoz, M; Navas-Flores, A (Mathematical Sciences Publishers, 2016)
Burago and Kleiner and, independently, McMullen, gave examples of Delone sets (that is, subsets of Euclidean space that are discrete and separated in a uniform way) that are non-bi-Lipschitz equivalent to the standard lattice. We refine their methods of construction via a discretization technique, thus giving the first examples of Delone sets as above that are also repetitive, in the sense that a translated copy of each patch appears in every large enough ball. © 2016 Mathematical Sciences Publishers. All rights reserved.